2015
DOI: 10.1063/1.4914147
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the 900 cm−1 broad double-hump OH vibrational feature of strongly hydrogen-bonded carboxylic acids

Abstract: Medium and strong hydrogen bonds are common in biological systems. Here, they provide structural support and can act as proton transfer relays to drive electron and/or energy transfer. Infrared spectroscopy is a sensitive probe of molecular structure and hydrogen bond strength but strongly hydrogen-bonded structures often exhibit very broad and complex vibrational bands. As an example, strong hydrogen bonds between carboxylic acids and nitrogen-containing aromatic bases commonly display a 900 cm(-1) broad feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
(55 reference statements)
2
35
0
Order By: Relevance
“…These interpretations are corroborated by Van Hoozen and Petersen, who analyzed the broad solution-phase OH stretching transitions observed in a series of carboxylic acid/nitrogen-containing aromatic base H-bonded dimers. These model dimers display complicated OH stretching transitions with multiple broad humps spanning ∼1000 cm –1 in solution. The computational models developed by Van Hoozen and Petersen took into account Fermi-resonance coupling between the OH stretch and OH bending modes and coupling to low-frequency H-bond stretching motion between the monomers.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These interpretations are corroborated by Van Hoozen and Petersen, who analyzed the broad solution-phase OH stretching transitions observed in a series of carboxylic acid/nitrogen-containing aromatic base H-bonded dimers. These model dimers display complicated OH stretching transitions with multiple broad humps spanning ∼1000 cm –1 in solution. The computational models developed by Van Hoozen and Petersen took into account Fermi-resonance coupling between the OH stretch and OH bending modes and coupling to low-frequency H-bond stretching motion between the monomers.…”
Section: Discussionmentioning
confidence: 70%
“…The calculations showed that the hump substructure can be attributed to the OH stretch-bend Fermi-resonance interactions modes, while the overall breadth originates from low-frequency motions that modulate H-bond distances and thus the frequency of the OH stretch. The calculations also predicted the OH stretch to have an intrinsic (0 K) line width of >200 cm –1 due to the distribution of H-bond distances between monomers at the zero-point level . Critically, these computational models demonstrated that the OH stretch frequency modulation induced by low-frequency H-bond stretching motions also strongly modulates the OH stretch-bend Fermi-resonance coupling …”
Section: Discussionmentioning
confidence: 84%
“…The neglect of water bending vibrations, Fermi resonance, and dynamical coupling between OH vibrational modes (as well as the fact that the calculated flanking water spectra are obtained from the nearest, non-over-coordinated, water molecule), are all expected to contribute to the relatively small differences between the shapes of the calculated and measured IR spectra. 44 The neglect of coupling is expected to have a quantitative, but not a qualitative, influence on the overall spectrum, as the strength of the neglected coupling is expected to be substantially less than the ∼500 cm −1 widths of the excess proton and flanking water spectra. Note that in pure liquid water the maximum value of the intra-and intermolecular coupling between OH vibrations is about 50 cm −1 .…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…Because the interaction between the proton and surrounding water is effectively a strong charge–dipole interaction, it is not too surprising that GGA functionals like BLYP succeed in capturing the local solvation environment of the proton as observed in previous theoretical and experimental studies. It is also worth stressing that, while the AIMD configurations we used are sampled from classical simulations, some nuclear quantum effects (such as proton delocalization and ZPE) are included in the subsequent IR and Raman spectral calculations. The neglect of water bending vibrations, Fermi resonance, and dynamical coupling between OH vibrational modes (as well as the fact that the calculated flanking water spectra are obtained from the nearest, non-over-coordinated, water molecule), are all expected to contribute to the relatively small differences between the shapes of the calculated and measured IR spectra . The neglect of coupling is expected to have a quantitative, but not a qualitative, influence on the overall spectrum, as the strength of the neglected coupling is expected to be substantially less than the ∼500 cm –1 widths of the excess proton and flanking water spectra.…”
mentioning
confidence: 99%
“…In the bulk, it has been shown that broadness in the vibrational spectrum results from the distribution of geometries. ,, The oscillations of hydrogen bonds are sensitive to the slight changes in the local surroundings and the exact geometry of the system. Further, some of the unusual line shape features of vibrational spectra are caused by Fermi resonance (a quantum mechanical coupling phenomenon) interactions. Also, the vibrational relaxation time for an excited group can be extremely short leading to the homogenous line shape broadening of its adsorption band. , Similarly, the broadness and spectral features at the solid/liquid interface can result from a variety of reasons. The potential reasons could be the heterogeneity of the surface, roughness of the solid surface, orientation of the liquid molecules next to solid surface, ,, packing of molecules next to solid surface, dynamics of surface hydrogen bonds, multiple interactions between the liquid molecule and solid surface, , liquid molecular size, and the lattice spacing of the solid crystal structure .…”
Section: Introductionmentioning
confidence: 99%